Solar Panel Efficiency Enhancement through Water Cooling with IoT Integration - BimaJaya, Adam; Permana, Agustian Damar; Devitra, Heldy (MSD Institute, 2025)
The efficiency of photovoltaic (PV) solar panels declines significantly with increasing temperature due to the thermal sensitivity of semiconductor materials. To mitigate this issue, various cooling strategies—particularly water-based systems—have been explored. This study presents the design and implementation of an Internet of Things (IoT)-based monitoring system to assess the impact of water cooling on PV panel performance. Experiments were conducted in a laboratory environment using observational methods, with data collected at 30-second intervals and visualized via the ThingSpeak platform. Results show that panels equipped with water cooling maintained lower operating temperatures and generated higher average voltage outputs than non-cooled counterparts. These findings confirm a positive correlation between temperature reduction and enhanced panel efficiency. While current measurements were not directly analyzed due to the system’s solar charge controller (SCC) configuration, the overall setup proved effective for real-time performance monitoring and demonstrates the potential of IoT integration in optimizing solar energy systems, particularly for large-scale applications.